2009
DOI: 10.1175/2008mwr2597.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of WRF Forecasts of Tornadic and Nontornadic Outbreaks When Initialized with Synoptic-Scale Input

Abstract: Uncertainty exists concerning the links between synoptic-scale processes and tornado outbreaks. With continuously improving computer technology, a large number of high-resolution model simulations can be conducted to study these outbreaks to the storm scale, to determine the degree to which synoptic-scale processes appear to influence the occurrence of tornado outbreaks, and to determine how far in advance these processes are important. To this end, 50 tornado outbreak simulations are compared with 50 primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 61 publications
6
39
1
Order By: Relevance
“…The low-level SRH, can vary dramatically over short distances, due to topographically channeled flow (e.g., Braun and Monteverdi, 1991;Bosart et al, 2006). The selection of these parameters is consistent with the approach adopted in previous studies (Droegemeier et al, 1993;Johns et al, 1993;Rasmussen and Blanchard, 1998;Brooks et al, 2003;Doswell and Evans, 2003;Thompson et al, 2003;Shafer et al, 2009;Matsangouras et al, 2011aMatsangouras et al, , 2012Sioutas et al, 2012). Table 1.…”
Section: T Matsangouras Et Al: Effect Of Topography On Tornadogesupporting
confidence: 69%
“…The low-level SRH, can vary dramatically over short distances, due to topographically channeled flow (e.g., Braun and Monteverdi, 1991;Bosart et al, 2006). The selection of these parameters is consistent with the approach adopted in previous studies (Droegemeier et al, 1993;Johns et al, 1993;Rasmussen and Blanchard, 1998;Brooks et al, 2003;Doswell and Evans, 2003;Thompson et al, 2003;Shafer et al, 2009;Matsangouras et al, 2011aMatsangouras et al, , 2012Sioutas et al, 2012). Table 1.…”
Section: T Matsangouras Et Al: Effect Of Topography On Tornadogesupporting
confidence: 69%
“…Generally speaking, the troughs associated with the NTOs all have a positive tilt that is far less amplified. The amplification of these tilts in the TO events suggests an increase in storm-relative environmental helicity (SREH) and vertical bulk shear in the TOs, as in previous work (e.g., M09; S09; Shafer et al 2010).…”
Section: A Interpretation Of the Synoptic Pattern Compositessupporting
confidence: 68%
“…Most NTO composites had marginal shear and SREH magnitudes relative to the TO composites both in the original composite fields and in the WRF simulations of the composites. The study revealed a classical synopticscale pattern for a typical major TO with minor deviations (e.g., the tilt of the trough at 850 mb), but several types of NTOs resulted from the analysis, likely attributable to the known seasonality of NTOs (Shafer et al 2010). Overall, the results demonstrate clear synopticscale differences between the two outbreak types, and the WRF simulations support that conclusion.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Simulations of the top 50 TOs and NTOs from D06 were conducted at 24-, 48-, and 72-h lead times (see Shafer et al 2009 for a detailed review of the simulation process). One NTO event, 5 July 1980, had a 1200 UTC valid time (as opposed to the 0000 UTC valid time for the remaining 99 cases), so it was rejected.…”
Section: A Data and Wrf Model Simulationmentioning
confidence: 99%